In-line physical desorption unit—Part 2: Optimisation analysis - Ban, Z.H. (Institution of Chemical Engineers, 2017)
This paper is the second part of our study on a novel in-line physical desorption unit. In the first part, the conceptual design and desorption modelling were discussed. In this paper, the work was extended to the optimisation and numerical analysis on the optimised desorption unit design. Similar to first part of our study, the desorption phenomenon was modelled via Computational Fluid Dynamics (CFD) approach. The desorption performance for seven different design parameters were studied and analysed via design of experiment (DOE) method. The objective functions were analysed and the suggested optimised design parameters were determined. Thereafter, the detailed hydrodynamics and mass transfer profile in the suggested optimised designs were simulated and studied. The performances of the optimised designs were found better than conventional nozzle. The solvent velocity at the outlet was found to be relatively high, which was ideal to be utilised together with compact gas liquid separator. The proposed in-line physical desorption unit has potential to be employed in various process conditions including remote and offshore conditions. © 2016 Institution of Chemical Engineers